АДМИНИСТРАТИВНО ПРАВОВАЯ ПРЕЮДИЦИЯ И ПРОФИЛАКТИКА ПРЕСТУПНОСТИ (Journal of actual problems of jurisprudence, 2019)
Summing up it is recommended for the above when creating certain articles of disposition should be guided by the provisions of the criminal code.application of the Institute of administrative and legal prejudice.